Determining factors of curtailment and purchasing energy related behaviours. (20th January 2016) - Testa, F.; Cosic, A.; Iraldo, F.
Abstract: Changing people's behaviour in relation to energy consumption will be one of the most important challenges in the near future. We analyzed the determinants behind individuals' decisions to adopt curtailment behaviour or to purchase energy saving products. Using data from 213 university students, we explored the influence of personal capabilities and moral norms, along with trust in information on energy saving actions provided by different entities on two energy saving behaviours. The results of the statistical model emphasise how personal norms and trust in information provided by private companies, on the one hand, and family and friends, on the other, strongly influence the adoption of energy saving actions and curtailment behaviours. The paper reveals the pivotal role of private companies in developing the market demand for energy-saving products by providing credible and scientifically-based information on environmental performance. The paper also contributes to strengthening the reliability of value-belief-norm theory and emphasizes the role of trust in information as a contextual factor that influences the adoption of a pro-environmental behaviour.